THE CHOICE OF SELECTION CRITERIA FOR CHILI (Capsicum annuum L) ASSEMBLY IN PEATLAND - Harry Sugestiadi; Nurbaiti '; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research was to determine about information the choice ofselection criteria on chile varieties assembly in peatland. The research usedRandomized Block Design (RBD) consisted of 20 treatments with threereplications. The treatment consisted of 20 genotypes of chili that is genotype C2,C120, C51, C111, C105, C117, C118, C157, C159, F5110005-91-13-5,F5110005-91-13-12, F8002005-2-9-12-1, C140, C5, C18, C19, C143, F512005-5-11-1, C145 and C160. The data were analyzed by analysis of variance, furthertest DNMRT at 5% level and Pearson’s correlation. Parameters observed were:the age of flower appearance, height dichotomous, plant height, stem diameter,canopy width, leaf length, leaf width, age of harvest, fruit length, fruit stalklength, fruit diameter, weight per fruit and weight of fruit per plant. The resultsshowed that there is a positive correlation between the parameters of weight perfruit, fruit length, fruit stalk length, leaf width and leaf length to weight of fruit perplant.C143 is a genotype that has the highest value of weight per fruit. GenotypeC111 has the highest value of fruit lenght and fruit stalk length. Genotype C51has the highest value of leaf width and genotype F5110005-91-13-12 has thehighest value of leaf length.Keyword : Chili, Selection, Correlation, Peatland